The effect of small-scale changes in wealth on risk attitudes: an experimental study - Sergio Almeida (EconomiA, 2023)
Purpose: This study aims to examine the effects of prior small-scale changes to wealth on subsequent risky choices. Design/methodology/approach: The paper opted for a laboratory experiment in which subjects perform two sequences of risky tasks. In between these two sets, the author transfers money for real for a randomly selected half of the subjects. Data on choices before and after the transfer of money are used to estimate risk attitudes and analyze whether the transfer of money affected attitudes to risk. Findings: The author finds that the money gain does not change subjects' risk preferences - neither in a within- nor in a between-subject design. This suggests that individuals' risky choices are consistent with their constant absolute (CARA) risk aversion preferences, a result that supports a key assumption in recent literature on the calibration critique of decision theories and the view that individuals engage in narrow framing. Research limitations/implications Because of the relatively small transfer of money, the research results may lack generalizability. Practical implications The paper includes implications for the reference-dependent and other theories that explain how prior outcomes affect risk-taking behavior in sequential problems. Social implications The results are relevant to the research community studying risk-taking behavior as the results shed new light on a well-known result put forward by a seminal paper by Thaler. Originality/value: This paper fills in an identified gap in the literature which is the need to test the house-money effect in a more realistic setting (over repeated risk-elicitation tasks, with money given outside the lotteries and in a within-subject design).
Keywords: 330; Risk-taking; Small-scale wealth effect; House money effect; Earned money